(untitled) (ENTHYMEMA, 2012)
Alfonso Gatto made his intimate pictorial ambition public for the first time in 1943 in Milan with his personal exhibition at the Galleria dell’Annunciata. After twenty-six years, once more in Milan, at the Galleria del Naviglio, the poet exhibited a collection of one hundred paintings, all produced with the intention to give life to a work that would bring together words and images. We can find a poetic track of this project in the volume Rime di viaggio per la terra dipinta, which was published without its iconographic counterpart by the will of the publisher. The finding of a photographic archive related to the original paintings allowed to match the poetic compositions with their figurative sources and to reach a more complete overall reading of the whole artistic project.